The Empowerment of National Defense in Realizing the Fulfillment of the Minimum Essence Force (MEF) By the Domestic Defense Industry - Wachit Hasim (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
In writing this paper, the author gives the title Empowerment of National Defense in Realizing the Fulfillment of the Minimum Essence Force (MEF) by the Domestic Defense Industry, which will briefly discuss the use of challenges and opportunities in efforts to empower the national defense industry to meet the MEF target of the TNI's leading defense equipment. In line with the need for military weapons. The writing of this paper aims to provide benefits in the form of contribution of thoughts to the leadership of the Navy from an educative, inspiring, and instructive aspect as well as consideration for the leadership of the Navy in an effort to build by encouraging, motivating, and raising awareness of its potential and trying to develop it, so that it can support the empowerment of national defense in realizing the fulfillment of the Minimum Essence Force (MEF) of the TNI's defense equipment, especially the Navy, by the domestic defense industry. In writing this group papper, we use a descriptive historical analysis method conducted comprehensively. The approach used in writing this paper uses a literature study approach, theoretical, juridical, and empirical assignment. In the discussion of writing this paper, to be able to find out the achievements of the Minimum Essence Forces (MEF) posture, to know the condition of the defense industry, and to know the challenges and solutions for the Indonesian Defense Industry to face these challenges is a strong commitment and systematic planning in strengthening the synergy between ministries and institutions. The conclusion in writing this paper is that the empowerment of the national defense industry in supporting the needs of national defense requires a long process, and its implementation requires continuity.